Savings, asset holdings, and temporary migration - Christian Dustmann; Josep Mestres (Institute for the Study of Labor (IZA), 2011)
This paper analyzes savings and asset holdings of immigrants in relation to their return plans. We argue that savings and asset accumulation may be affected by return plans of immigrants. Further, the way savings and assets are held in the home- and host country may also be related to future return plans. Thus, comparing savings and assets between immigrants and natives may lead to serious underestimation when neglecting the home country component. We show that immigrants with temporary return plans place a higher proportion of their savings in the home country. In addition, both the magnitude and the share of assets and housing value accumulated in the home country are larger for immigrants who consider their migration as temporary, and lower the value of assets and property held in the host country. Finally, and conditional on observable characteristics, we find no evidence that immigrants with temporary migration plans save more than immigrants with permanent migration plans.
urn:nbn:de:101:1-201104113715
Keywords: F22; D31; R21; 330; international migration; wealth accumulation; housing demand; Migranten; Sparen; Vermögensbildung; Besitzformwahl; Rückwanderung; Vergleich; Bevölkerung; Deutschland